2016
DOI: 10.3892/mmr.2016.6099
|View full text |Cite
|
Sign up to set email alerts
|

Role of tRNA selenocysteine 1 associated protein 1 in the proliferation and apoptosis of cardiomyocyte-like H9c2 cells

Abstract: Transfer RNA selenocysteine 1 associated protein 1 (Trnau1ap) serves an essential role in the synthesis of selenoproteins, which have critical functions in numerous biological processes. Selenium deficiency results in a variety of diseases, including cardiac disease. However, the mechanisms underlying myocardial injury induced by selenium deficiency remain unclear. The present study examined the effects of Trnau1ap under‑ and overexpression in cardiomyocyte‑like H9c2 cells, by transfection with small interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Research investigating the aberrant molecular processes that occur during cardiac hypertrophy has used primary cardiomyocytes from neonatal rat hearts as the standard experimental in vitro system. In addition, some studies have made use of the H9C2 rat cardiomyoblast cell line ( 38 , 39 ), as it was found by Watkins et al ( 40 ) that the H9C2 cell line and primary neonatal cardiomyocyte cells exhibit similar hypertrophic responses in vitro . Therefore, the H9C2 cell line was selected for the present study, which also has the advantage of being an animal-free alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the aberrant molecular processes that occur during cardiac hypertrophy has used primary cardiomyocytes from neonatal rat hearts as the standard experimental in vitro system. In addition, some studies have made use of the H9C2 rat cardiomyoblast cell line ( 38 , 39 ), as it was found by Watkins et al ( 40 ) that the H9C2 cell line and primary neonatal cardiomyocyte cells exhibit similar hypertrophic responses in vitro . Therefore, the H9C2 cell line was selected for the present study, which also has the advantage of being an animal-free alternative.…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, Myc upregulates the expression of genes associated with RNA metabolism, protein metabolism, ribosome biogenesis and ribosome function (32). Additionally, Myc controls the expression of selenocysteine biosynthesis, ornithine decarboxylase and lactate dehydrogenase A, all of which promote cell proliferation in other cell types (146)(147)(148).…”
Section: From Harmful To Necessary: Myc Effects On Pancreatic β-Cell mentioning
confidence: 99%
“…описано усиление каспаза-3-зависимого апоптоза в различных тканях позвоночных при селенодефиците [87]. [87,88]. Выход цитохрома с из митохондрий также зависит от активности каспаз -1 и -7.…”
Section: селенодефицит вызывает воспалениеunclassified